Nanoscale Double‐Heterojunctional Electrocatalyst for Hydrogen Evolution. Issue 18 (24th April 2022) - Feng, Yangyang; Guan, Yongxin; Zhou, Enbo; Zhang, Xiang; Wang, Yaobing
Abstract: The active sites and charge/mass transfer properties in electrocatalysts play vital roles in kinetics and thermodynamics of electrocatalysis, and impose direct impacts on electrocatalytic performance, which cannot be achieved by a simplex structure. As a prototype, the authors propose a double‐heterojunctional nanostructure of NiS2 /Ni3 C@C containing NiS2 /Ni3 C and Ni3 C/C heterojunctions as a general model to optimize the above issues and boost electrocatalytic performance. During the thermal reorganization, the in situ reaction between NiS2 nanoparticles and carbon induces the formation of Ni3 C between them and constructs tightly contacted two kinds of interfaces among the three components. The TEM and XPS reveal the intimately contacted three components and the as‐constructed interacted dual interfaces, further confirming the formation of a porous double‐heterojunctional nanostructure. Theoretical calculations uncover that the electron density redistribution occurs at Ni3 C/C interface by spontaneous electron transfer from defected carbon to Ni3 C and lower ΔGH* achieves at NiS2 /Ni3 C interface by the concentrated interfacial charge density, which favors the simultaneous realization of high catalytic activity and rapid charge/mass transfer. When applied for hydrogen evolution reaction (HER), the porous double‐heterojunctional NiS2 /Ni3 C@C exhibits excellent HER activity and durability among all pH values. Profoundly, this special double‐heterojunctional structure can provide a new model for high‐performance electrocatalysts and beyond. Abstract : Nanoscale double‐heterojunctional NiS2 /Ni3 C@C is first proposed for electrocatalysis as a general model to simultaneously achieve high catalytic activity and rapid charge/mass transfer. The DFT calculations uncover that the Ni3 C/C heterojunction rearranges the electron density and promotes spontaneous electron/mass flow accessible to catalytic active sites, and the NiS2 /Ni3 C heterojunction tunes the electron cloud density and enhances the catalytic activity.